Electrophysiological Screening for Children With Suspected Auditory Processing Disorder: A Systematic Review - Liu, Panting; Zhu, Huiqin; Chen, Mingxia; Hong, Qin; Chi, Xia (Frontiers in Neurology, 2021)
Objective This research aimed to provide evidence for the early identification and intervention of children at risk for auditory processing disorder (APD). Electrophysiological studies on children with suspected APDs were systematically reviewed to understand the different electrophysiological characteristics of children with suspected APDs. Methods Computerized databases such as PubMed, Cochrane, MEDLINE, Web of Science, and EMBASE were searched for retrieval of articles from the database's establishment through May 18, 2020. Cohort, case-control, and cross-sectional studies that evaluated the literature for the electrophysiological assessment of children with suspected APD were independently reviewed by two researchers for literature screening, literature quality assessment, and data extraction. The Newcastle–Ottawa Scale and 11 entries recommended by the Agency for Healthcare Research and Quality were used to evaluate the quality of the literature. Results In accordance with the inclusion criteria, 15 articles were included. These articles involved 8 electrophysiological testing techniques: click-evoked auditory brainstem responses, the binaural interaction component of the auditory brainstem responses, maximum length sequences–auditory brainstem responses, the speech-evoked auditory brainstem response, the middle-latency response, cortical auditory evoked potential, mismatch negativity, and P300. The literature quality was considered moderate. Conclusions Auditory electrophysiological testing can be used for the characteristic identification of children with suspected APD; however, the value of various electrophysiological testing methods for screening children with suspected APD requires further study.